Adverse Drug Reactions: Recognition, Management, And Prevention (Journal of Namibian Studies : History Politics Culture, 2023)
Adverse drug reactions (ADRs) are unintended and harmful responses to medications, posing significant challenges in healthcare due to their potential impact on patient safety and treatment outcomes. Recognizing, managing, and preventing ADRs require a comprehensive approach that integrates patient history, clinical assessment, pharmacological knowledge, and proactive measures to promote safe medication use. This article provides an overview of ADR recognition, management, and prevention strategies in clinical practice. Key topics discussed include patient history-taking, clinical assessment of ADRs, pharmacological interventions, supportive care measures, and preventive strategies such as medication reconciliation, rational drug prescribing, patient education, and pharmacovigilance. By implementing these preventive measures, healthcare providers can reduce the incidence of ADRs, enhance patient safety, and improve overall healthcare quality.